Is the Health Behavior in School-Aged Survey Questionnaire Reliable and Valid in Assessing Physical Activity and Sedentary Behavior in Young Populations? A Systematic Review - Su, Yang; Zhang, Yanjie; Chen, Si-Tong; Hong, Jin-Tao; Wang, Hongying (Frontiers in Public Health, 2022)
Backgrounds: Using the self-reported questionnaire to assess the levels of physical activity (PA) and sedentary behavior (SB) has been a widely recognized method in public health and epidemiology research fields. The selected items of the Health Behavior in School-aged (HBSC) Survey Questionnaire have been used globally for measurements and assessments in PA and SB of children and adolescents. However, there is no comprehensive and critical reviews to assess the quality of studies on reliability and validity of selected items for PA and SB measurement and assessment derived from the HBSC. Thus, this review aimed to critically assess quality of those studies and summary evidence for future recommendations. Methods: A systematic review protocol was used to search potentially eligible studies on assessing reliability and validity of PA and SB measures of the HBSC questionnaire. electronically academic databases were used. The information on reliability and validity of the PA and SB measures were extracted and evaluated with well-recognized criterion or assessment tools. Results: After literature search, 6 studies were included in this review. The reliability of PA measures of the HBSC questionnaire showed a moderate agreement while the reliability of SB measures showed a great variation across the different items in the different subgroups. The validity of the PA measures had an acceptable performance, whereas no studies assess the validity of the SB measures. The included studies all had quality weakness on reliability or validity analysis. Conclusions: The PA and SB measures of the HBSC questionnaires were reliable in assessing PA and SB among adolescents. However, a little evidence showed that PA measures are partially valid in assessing PA, but no evidence confirmed the validity of SB measures. The included studies all had methodological weakness on examining the reliability and validity of the PA and SB measures, which should be addressed in the future. Further studies are encouraged to use more standardized study design to examine the reliability and validity of the PA and SB measures in more young populations.